Sistem Informasi Inventarisasi Sumberdaya Perikanan Kabupaten Maluku Tenggara Dengan Metode Rapid Application Development Berbasis Web - Lidya Elsye Reniban (Universitas Bina Sarana Informatika, 2019)
- Southeast Moluccas Regency is a districts in Moluccas Province that is rich in marine fisheries resources, especially pelagic fish, seaweed, and demersal fish. Knowledge of information fisheries resources by fishermen and the community in general in the regions is still low, because the unavailability of easy information media to access information about fisheries resources in this area. The research aims to design an information system of fisheries resources inventory to improve the performance of the Southeast Moluccas Regency Government to inform and process data on fisheries resources. System design method uses RAD (Rapid Application Development). System design tools use UML (Unified Modeling Language), to make applications using the PHP(Hypertext Preprocessor) programming language, and MySQL as the database. Information System for Fisheries Resources has been tested using the blackbox method, the results show the system runs as expected. This system can display information on Southeast Moluccas Regency Fisheries Resources informally to the public and can be used as a tool for local governments to improve performance for presentation and processing of data and information in the marine and fisheries sector. Keywords: Information Systems,Inventory, Fisheries, RAD, UML